GAMBARAN PROSES PENGELOLAAN OBAT (STUDI KUALITATIF DI INSTALASI FARMASI RS MANEMBO-NEMBO BITUNG TIPE C) - Gayatri Citraningtyas; Imam Jayanto; Randy Tampa’i (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2021)
Medicine supply is one of the biggest components of budget expenditures at hospitals, so medicines must be managed effectively and efficiently according to Pharmaceutical Service Standards at hospitals. The purpose of this study was to evaluate the management of medicines in the Pharmacy Installation at Manembo Nembo Bitung Type C Hospital according to the standard of Permenkes Number 72 of 2016. This is descriptive research by taking data through interviews and observations. The result showed that the selection of medicines was based on the hospital formulary as well as the planning of consumption methods according to the budget of Manembo Nembo Bitung Type C Hospital. The procurement of medicines was carried out by the PPK team in the North Sulawesi Province through the e-catalog and or auction system. The receipt was carried out by the recipient team of Manembo Nembo Bitung Type C Hospital according to the order letter. Storage in the Pharmacy Installation of hospital drug warehouse is carried out by warehouse personnel. Distribution to outpatient using an individual prescribing system while inpatient using the UDD (Unit Dose Dispensing) system. Annihilation of medical waste and expired medicines is carried out every year through a third party. Medicines withdrawal is carried out by distributors through official circulars from BPOM. Stocktaking is done routinely by pharmacists. The administration of pharmaceutical activities is recorded by administrative staff and reported to the Head of IFRS and internal evaluation through monthly meetings. In conclusion, the management of medicines in Pharmacy Installation at Manembo Nembo Bitung Type C Hospital is following the standard of Permenkes Number 72 of 2016, but it still needs improvement in the controlling of medicine ordering time in the procurement process, special scheduling of pharmacists in clinical services and services in pharmacies due to limited human resources, recording and reporting that still done manually, and in evaluating that is limited to daily activities.